Media Penunjang Informasi Dan Promosi Berbentuk Katalog Produk Pada PT. Ideal Formica Purnatata Tangerang - Alin Parlina; Gita Mawarni; Dinda Safitri (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
Visual communications media plays an important role in the self-introduction a company primarily in supporting information and promotion. One of the visual communication media is very important in supporting the successful sale of the company is a media product catalog. Companies in need of information and promotional media such as print media, because the media is effective compared with other media such as video profile. PT. Ideal Formica Purnatata is a company engaged in the manufacture of products and architectural interiors. The purpose of this study, so that the company can achieve its sales target of each product marketed. To obtain accurate data in the preparation of the study, there is the research methodology used are: problem analysis methods, data collection methods, methods of design analysis and methods of design concepts. The problem that exists is the lack of information and promotional media such as media product catalog. Visual communication media has a method of designing one form of material used is 260 g carton art and art paper 120 gr. The choice of material is in use because of the materials according to the media catalog. Media design through product catalogs, is expected to increase the attractiveness of the consumer to use the services and products of PT. Ideal Formica Purnatata, so that the sales target is reached, the company's turnover increased, and PT. Ideal Formica Purnatata widely known.